Quantification of plasma remdesivir and its metabolite GS-441524 using liquid chromatography coupled to tandem mass spectrometry. Application to a Covid-19 treated patient - Alvarez, Jean-Claude; Moine, Pierre; Etting, Isabelle; Annane, Djillali; Larabi, Islam Amine (Clinical chemistry and laboratory medicine, 2020)
A method based on liquid chromatography coupled to triple quadrupole mass spectrometry detection using 50 µL of plasma was developed and fully validated for quantification of remdesivir and its active metabolites GS-441524. A simple protein precipitation was carried out using 75 µL of methanol containing the internal standard (IS) remdesivir-13C6 and 5 µL ZnSO4 1 M. After separation on Kinetex® 2.6 µm Polar C18 100A LC column (100 × 2.1 mm i.d.), both compounds were detected by a mass spectrometer with electrospray ionization in positive mode. The ion transitions used were m/z 603.3 → m/z 200.0 and m/z 229.0 for remdesivir, m/z 292.2 → m/z 173.1 and m/z 147.1 for GS-441524 and m/z 609.3 → m/z 206.0 for remdesivir-13C6. Calibration curves were linear in the 1-5000 μg/L range for remdesivir and 5-2500 for GS-441524, with limit of detection set at 0.5 and 2 μg/L and limit of quantification at 1 and 5 μg/L, respectively. Precisions evaluated at 2.5, 400 and 4000 μg/L for remdesivir and 12.5, 125, 2000 μg/L for GS-441524 were lower than 14.7% and accuracy was in the [89.6-110.2%] range. A slight matrix effect was observed, compensated by IS. Higher stability of remdesivir and metabolite was observed on NaF-plasma. After 200 mg IV single administration, remdesivir concentration decrease rapidly with a half-life less than 1 h while GS-441524 appeared rapidly and decreased slowly until H24 with a half-life around 12 h. This method would be useful for therapeutic drug monitoring of these compounds in Covid-19 pandemic.